2018
DOI: 10.4022/jafib.1797
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Approach to the Different Parts of Vasovagal Syncope in a Patient Undergoing Cardioneuro Ablation

Abstract: A 30-year-old man underwent ganglionated plexi ablation due to cardioinhibitory type vasovagal syncope with asystole. After asymptomatic period of 15-month following the procedure, the patient experienced 2 new syncope episodes. Tilt test demonstrated vasodepressor response without significant bradycardia. Following the onset of midodrine therapy, the patient was asymptomatic for 1 year and tilt test demonstrate normal response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Pachon et al [6] reported cardiac autonomic modulation through catheter ablation guided by fast Fourier transformation analysis as an alternative treatment of functional bradycardias. Several other case reports and case series have also suggested that GP ablation is effective for patients suffering from neurocardiogenic syncope [7][8][9][10], however, it is unclear whether GP ablation is effective for the patient with nocturnal bradyarrhythmias. In the present case, post-procedure 24-h Holter ECG and ILR recordings showed that GP ablation could be an effective therapeutic approach to achieve long-term vagal attenuation to prevent functional AV block and sinus bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“…Pachon et al [6] reported cardiac autonomic modulation through catheter ablation guided by fast Fourier transformation analysis as an alternative treatment of functional bradycardias. Several other case reports and case series have also suggested that GP ablation is effective for patients suffering from neurocardiogenic syncope [7][8][9][10], however, it is unclear whether GP ablation is effective for the patient with nocturnal bradyarrhythmias. In the present case, post-procedure 24-h Holter ECG and ILR recordings showed that GP ablation could be an effective therapeutic approach to achieve long-term vagal attenuation to prevent functional AV block and sinus bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“…Syncope recurred in only 3 cases during follow-up (2 vasodepressor, 1 undefined). Recently, more evidence ( 5 , 6 , 7 , 8 ) on the safety and efficacy of GP ablation for VVS has emerged, most of which were about type 1 or 2 syncope involving bradycardia or functional AV block. The anatomy or HFS-guided GP targets covering both the RA and left atrium (LA), including the left superior/inferior GP and right anterior/inferior GP, are consistent with our ablation locations ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more evidence ( 5 , 6 , 7 , 8 ) on the safety and efficacy of GP ablation for VVS has emerged, most of which were about type 1 or 2 syncope involving bradycardia or functional AV block. The anatomy or HFS-guided GP targets covering both the RA and left atrium (LA), including the left superior/inferior GP and right anterior/inferior GP, are consistent with our ablation locations ( 7 ). Type 3 patients (vasodepressor response) have been rarely attempted in previous studies, although mixed types (cardioinhibitory and vasodepressor) have shown favorable response ( 4 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the prevalence of treatment failure in VVS, combined with the fraught pursuit of permanent pacing in a relatively young patient population, minimally invasive denervation has been pioneered in recent years via radiofrequency (RF) cardioneuroablation (CNA). 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 However, while recurrent syncope following CNA has been described, there have not been reports of recurrence coinciding with objective data reflecting the return of parasympathetic autonomic function. Herein we describe such a case, documenting cardioinhibitory VVS recurrence post-CNA with the use of an implantable loop recorder (ILR).…”
Section: Introductionmentioning
confidence: 99%